Recurrent madura foot without draining sinuses: a case report - Mahakalkar, Chandrashekhar C.; Yeola, Meenakshi; Tote, Darshana; Jain, Jalaj; Jain, Niket (International Journal of Research in Medical Sciences, 2017)
Madura foot or mycetoma is a chronic granulomatous disease characterized by localized infection of subcutaneous tissues by actinomycetes or fungi. The recurrence rate for the disease if treated inadequately is very high. Recurrence presents with swelling and multiple discharging sinuses. This is an unusual presentation of the disease without discharging sinuses which is probable the first report of this kind in the literature. A 34 year old, male, presented with the painless, progressive swellings over right foot since 4 years. No sinuses or discharge could be found on skin surface. The postoperative recurrence rate is very high, and this can be local or distant at the regional lymph nodes. This could be due to the disease biology and behavior or inadequate surgical excision. Usually it presents with multiple sinus tracts, and granule. We reported a case with classical absence of sinus tracts in recurrent actinomycosis.